Interaction Between Rhizoctonia solani and Meloidogyne hapla on Radish in Gnotobiotic Culture - KHAN, M. WAJID; MULLER, J. (The Libyan Journal of Agriculture, 2023)
There have been relatively few attempts to study the interaction between rootinfecting fungi and nematodes in gnotobiotic cultures in agar medium. In this study of interaction between Rhizoctonia solani and Meloidogyne hapla on radish (Raphanus sativus) in gnotobiotic culture in petri-plates, it was observed that prior infection of roots by nematode favoured the colonizing capability of the fungus. Galls were preferred by the fungus and mycelium accumulated over them. Vigorous mycelial growth and abundant sclerotial formation was observed on galls. Extensive necrosis of galls due to penetration of fungal hyphae resulted and roots became obliterated and whole galled tissue was colonized. Non-galled portions did not show sclerotial formation, but more hyphal growth and penetration was observed in contrast to the roots inoculated wth fungus alone. This indicates that the apparent physiological changes, especially, in the galled regions due to nematode infection pre-disposed the roots for invasion and rapid colonization by the fungus.